2005
DOI: 10.1248/bpb.28.2120
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ginseng Saponins on a Rat Visceral Hypersensitivity Model

Abstract: One of the most common gastrointestinal disorders without direct bacterial or viral infection is irritable bowel syndrome (IBS), which is strongly associated with stress. The most common IBS symptoms are abnormal visceral discomfort, pain and diarrhea. Although the precise mechanism of IBS has not been fully elucidated, some symptoms of IBS are thought to involve the 5-hydroxytryptamine receptor 3 (5-HT 3 ). Zacopride, a 5-HT 3 -receptor antagonist, has been used to effectively treat diarrhea-predominant IBS p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Nausea and vomiting are significant adverse effects of anti-cancer agents such as cisplatin, and cause significant patient morbidity. 5-HT 3 receptors are involved in vomiting and irritable bowel syndrome (Kim et al, 2005a,b). Ginsenoside-mediated action of 5-HT 3A receptor channel activity may be the molecular basis of the anti-vomiting action of ginseng.…”
Section: A Linkage Of the Ginsenoside-mediated Ion Channels And Recepmentioning
confidence: 99%
“…Nausea and vomiting are significant adverse effects of anti-cancer agents such as cisplatin, and cause significant patient morbidity. 5-HT 3 receptors are involved in vomiting and irritable bowel syndrome (Kim et al, 2005a,b). Ginsenoside-mediated action of 5-HT 3A receptor channel activity may be the molecular basis of the anti-vomiting action of ginseng.…”
Section: A Linkage Of the Ginsenoside-mediated Ion Channels And Recepmentioning
confidence: 99%
“…It was further reported that the activity of natural killer cells and lymphocyte-activated killer cells was significantly increased in the peripheral blood of patients undergoing radiotherapy with simultaneous administration of ginseng polysaccharides compared to patients not receiving ginseng polysaccharides. Moreover, one of the future promising effects of ginseng is treatment of the irritable bowel syndrome (IBS) since it was shown that protopanaxatriol (PT) ginsenosides attenuated the experimentally-induced visceral hypersensitivity (130). Sparsely, ginseng has been reported to possess positive effects against herpes simplex type-II infections and diabetes mellitus, common cold symptom complex, ethanol-induced gastric lesion, and aspirin-induced gastric ulcers (131).…”
Section: Clinical Aspects Of Ginsengmentioning
confidence: 99%
“…The success of DKT in the treatment of abdominal bloating in the present randomized controlled trial may be attributed to two interesting pharmacological effects reported in previous basic studies. The first is the improvement of GI motility via TRIPV1, TRIPA1, or motilin, 14,18,34 and the second is the possible improvement in visceral hypersensitivity due to its anti‐inflammatory effects 21 and antagonistic effects on 5‐HT 3A receptors in peripheral nerves 36 . Further study is necessary to clarify how these mechanisms of action of DKT affect abdominal bloating in humans.…”
Section: Discussionmentioning
confidence: 99%